2007
DOI: 10.1088/0954-3899/34/3/014
|View full text |Cite
|
Sign up to set email alerts
|

The neutron ‘thunder’ accompanying the extensive air shower

Abstract: Simulations show that neutrons are the most abundant component among extensive air shower hadrons. However, multiple neutrons which appear with long delays in neutron monitors nearby the EAS core ( 'neutron thunder' ) are mostly not the neutrons of the shower, but have a secondary origin. The bulk of them is produced by high energy EAS hadrons hitting the monitors. The delays are due to the termalization and diffusion of neutrons in the moderator and reflector of the monitor accompanied by the production of se… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…On the other hand, since the times when some evidences of an unexpectedly high neutron production within the core region of large sized extensive air showers were obtained in the experiments with the neutron monitor at the Tien Shan Cosmic Ray Station [15], a question arose on the behavior of low-energy (thermal and epithermal) neutron fluxes around the EAS center. The urgency of the analysis of lowenergy neutron component both in the central region and at the periphery of powerful EAS was discussed in various publications as well [21,22,23]. Consequently, a special experiment on registration of the flux of low-energy neutrons was fulfilled at the Tien Shan station in the end of 1990s [24].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, since the times when some evidences of an unexpectedly high neutron production within the core region of large sized extensive air showers were obtained in the experiments with the neutron monitor at the Tien Shan Cosmic Ray Station [15], a question arose on the behavior of low-energy (thermal and epithermal) neutron fluxes around the EAS center. The urgency of the analysis of lowenergy neutron component both in the central region and at the periphery of powerful EAS was discussed in various publications as well [21,22,23]. Consequently, a special experiment on registration of the flux of low-energy neutrons was fulfilled at the Tien Shan station in the end of 1990s [24].…”
Section: Introductionmentioning
confidence: 99%
“…Apparently, this radiation is emitted in the captures of thermal neutrons diffusing inside the polyethylene moderator of the neutron monitor, those neutrons, which originated in interactions of cosmic ray hadrons with the monitor's internal lead generator. In contradiction to [4,[8][9][10], the role of the external background of slow neutrons diffusing in the outer environment in generation of the delayed signal of soft radiation is not determinative.…”
Section: Measurements Of the Soft (Electromagnetic) Backgroundmentioning
confidence: 89%
“…A possible explanation for the existence of delayed signals in neutron monitor events was suggested in [9,10]. According to this hypothesis, intensive particle flows of an EAS, when passing through the atmosphere, generate a large amount of low-energy hadrons (these are nonrelativistic 100-200 MeV nucleons knocked-on from air nuclei and 5-30 MeV evaporation neutrons), which enter the monitor with some delay relative to the main EAS front and, by this way, are responsible for the delayed signals in neutron counters.…”
Section: Introductionmentioning
confidence: 98%
“…Given the complex and stochastic scattering processes that neutrons undergo as they thermalise with their surroundings, simultaneous measurements of both low and high energy neutrons across the full extent of an EAS are needed to understand the evolution of the neutron 'cloud' and its effects on water Cherenkov based cosmic ray detector arrays. In particular it has been shown that some component of the neutron signals observed in an extended air shower are the result of high energy electromagnetic particles interacting with detector materials, amplifying the delayed neutron signal [9].…”
Section: Introductionmentioning
confidence: 99%